Presentation of spinal cord and column tumors. (18th November 2020) - Fridley, Jared S; Syed, Sohail; Niu, Tianyi; Leary, Owen P; Gokaslan, Ziya L
Abstract: Metastatic spine disease occurs in more than 10% of all cancer patients. Advances in systemic treatment for cancer has led to improved overall survival for many types of cancer, which has increased the overall incidence of spinal metastases. The most common presenting complaint of patients with spinal metastases is pain. Pain originating from spinal metastases can be oncological, mechanical, and/or neurological in nature. Early recognition of these symptoms is helpful to guide treatment and accurately gauge patient prognosis. Unfortunately, the prevalence of degenerative back pain in the general population can complicate early clinical recognition of patients with metastatic spine disease. Therefore, back pain in any patient with a history of malignancy should prompt clinicians to perform an expedited workup for metastatic disease of the spine. Diagnostic imaging and laboratory studies are part of the initial work up. Obtaining pathology via biopsy to establish tumor histology is essential to determine the appropriate treatment.